A Cryptography and Machine Learning Based Authentication for Secure Data-Sharing in Federated Cloud Services Environment. Issue 3 (3rd July 2022) - Singh, Ashutosh Kumar; Saxena, Deepika
Abstract: Secure mutual authentication is an indispensable requirement to share organizational invaluable data among collaborating entities in federated cloud environment. This work presents a novel mutual authentication method which incorporates machine learning based ensemble Voting Classifier for online threat detection and Elliptic Curve Cryptography with Schnorr's signature scheme based key agreement to ensure secure communication among the participating entities by prior detection and mitigation of security breaches. The performance evaluation by using a benchmark from Canadian Institute for Cybersecurity Datasets and ProVerif security analysis tool verifies its efficiency in terms of security features and communication cost over existing approaches.